2002
DOI: 10.7589/0090-3558-38.3.511
|View full text |Cite
|
Sign up to set email alerts
|

Elemental and Organochlorine Residues in Bald Eagles From Adak Island, Alaska

Abstract: Adak Island is a remote island in the Aleutian Island archipelago of Alaska (USA) and home to various military activities since World War II. To assess the contaminant burden of one of Adak Island's top predators, livers and kidneys were collected from 26 bald eagle (Haliaeetus leucocephalus) carcasses between 1993 and 1998 for elemental and organochlorine analyses. Mean cadmium, chromium, mercury, and selenium concentrations were consistent with levels observed in other avian studies and were below toxic thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 12 publications
1
14
2
Order By: Relevance
“…Concentrations of Hg and/or Se in livers of common loons and bald eagles analyzed in the current study were comparable to ranges reported previously for these species (Wood et al 1996;Pokras et al 1998;Scheuhammer et al 1998;Bischoff et al 2002;Stout and Trust 2002;Weech et al 2004b). However concentrations of Hg and Se in brain tissue of these species have not been previously reported.…”
Section: Discussionsupporting
confidence: 83%
“…Concentrations of Hg and/or Se in livers of common loons and bald eagles analyzed in the current study were comparable to ranges reported previously for these species (Wood et al 1996;Pokras et al 1998;Scheuhammer et al 1998;Bischoff et al 2002;Stout and Trust 2002;Weech et al 2004b). However concentrations of Hg and Se in brain tissue of these species have not been previously reported.…”
Section: Discussionsupporting
confidence: 83%
“…Values of ␦ 15 N in fishes collected from 1999 to 2001 differed significantly among species ( f [2,54] ϭ 39.4, p Ͻ 0.0001) and islands ( f [5,54] ϭ 4.1, p ϭ 0.003), and differences among species were consistent among islands (species · island: f [10,54] ϭ 1.6, p ϭ 0.1; Table 3). Mean ␦ 15 N was highest in cod (14.0%), followed by halibut (12.8%) and greenling (12.1%).…”
Section: Stable Isotopesmentioning
confidence: 91%
“…A large Naval Air facility was located on the island from 1942 until 1997. Today about 200 people live in the island and there is an airport and a harbor [29], [37], [38]. Amchitka Island has also been subjected to military activities; it was a military base during World War II and it is one of the sites that comprise the Department of Energy's “Nuclear Weapons Complex”.…”
Section: Methodsmentioning
confidence: 99%